Evaluation of potential trap plant species for the wheat bug Nysius huttoni (Hemiptera: Lygaeidae) in forage brassicas. (30th April 2020) - Tiwari, Sundar; Saville, David J.; Sharma, Sheela; Shields, Morgan W.; Wratten, Stephen D.
Abstract: The wheat bug Nysius huttoni is a major pest of brassica seedlings. Management of this insect currently relies on seed treatment with neonicotinoids and spraying with chlorpyrifos and pyrethroid insecticides. These practices can generate severe external costs, including human health, the environment and biodiversity. Trap cropping is one alternative option to protect brassica seedlings from N. huttoni . Trap crop species evaluated in field cage experiments were: alyssum ( Lobularia maritima L. Desvauxcv. Benthamii White), wheat ( Triticum aestivum L. cv. Morph), coriander ( Coriandrum sativum L. cv. Santo) and clover ( Trifolium repens L. cv. Nomad). These were compared with kale ( Brassica oleracea L. cv. Kestrel). In open‐field experiments, alyssum ( L maritima ), wheat ( T. aestivum ) and a mixture of alyssum ( L. maritima ) and wheat ( T. aestivum ) were used. All of these were compared to kale ( B. oleracea ). Alyssum and wheat were the most favoured potential trap plants for N. huttoni . Results indicated that two treatments: alyssum (used as a single trap crop) or 'alyssum plus wheat' (a multiple trap crop), may be useful in brassica fields to protect the seedlings from N. huttoni damage. Such a trap cropping protocol potentially reduces pesticide use in forage brassicas and can also deliver multiple ecosystem services such as biological control of insect pests. Abstract : The endemic New Zealand wheat bug ( Nysius huttoni ) is a major threat to forage brassicas. Alyssum ( Lobularia maritima ) is the most effective trap crop for N. huttoni, followed by a multiple‐species trap cropping using a mixed crop of L. maritima and Triticum aestivum . Trap plants can reduce pesticide load and maintain ecosystem services in agricultural fields. Nysius huttoni population in potential trap plants.